Cardiovascular Effects of Trans-4-Methoxy-β-Nitrostyrene in Spontaneously Hypertensive Rats: Comparison With Its Parent Drug β-Nitrostyrene - Thayane Rebeca Alves-Santos; Odair Alves Silva; Hicla Stefany Moreira; Rosivaldo Santos Borges; Gloria Pinto Duarte; Pedro Jorges Caldas Magalhães; Saad Lahlou (Frontiers Media S.A., 2019)
We previously reported that trans-4-methoxy-β-nitrostyrene (T4MN) evoked higher vasorelaxant effects in small resistance arteries from spontaneously hypertensive rats (SHRs) in comparison with its parent drug, the β-nitrostyrene 1-nitro-2-phenylethene (NPe). To further our knowledge of the influence of insertion of an electron-releasing group such as methoxy in the aromatic ring of NPe, we investigated the cardiovascular responses to intravenous (i.v.) injection of T4MN in SHRs and compared with those of NPe. In anesthetized SHRs, i.v. treatment with T4MN (0.03-0.5 mg/kg) and NPe (0.03-3 mg/kg) induced dose-dependent bradycardia and hypotension, which were biphasic (named phases 1 and 2). Magnitude of these responses was significantly higher for T4MN compared with NPe. Phase 1 cardiovascular responses to both T4MN (0.3 mg/kg) and NPe (3 mg/kg) were prevented by cervical bivagotomy or perineural treatment of both cervical vagus nerves with capsaicin, but was unchanged by i.v. pretreatment with capsazepine or ondansetron. After injection into the left ventricle, NPe and T4MN no longer evoked phase 1 responses. In conscious SHRs, NPe (3 mg/kg, i.v.), and T4MN (0.3 mg/kg, i.v.) evoked monophasic hypotensive and bradycardiac effects which were suppressed by i.v. pretreatment with methylatropine. It is concluded that i.v. administration of NPe and T4MN in SHRs induced a vago-vagal hypotensive and bradycardic reflex that did not involve the activation of vanilloid TRPV1 or 5-HT3 receptors located on vagal pulmonary sensory nerves. With respect to its parent drug, T4MN was more potent in inducing this reflex. Phase 2 hypotensive response to i.v. NPe and T4MN seems partially resulting from a direct vasodilatory action. It seems that insertion of a methoxy group into the aromatic ring stabilized NPe, which in turn increases its cardiovascular effects.